Evaluation of the Combination of Metformin and Rapamycin in an MPP+-Treated SH-SY5Y Model of Parkinson's Disease. (16th January 2023) - Norradee, Chureerat; Khwanraj, Kawinthra; Balit, Tatcha; Dharmasaroja, Permphan
Abstract : Metformin (MET) and rapamycin (RAPA) have been reported to protect against neurodegeneration in cellular and animal models of Parkinson's disease (PD). MET, which is a first-line drug for type 2 diabetes, and RAPA are known as mTORC1 inhibitors. MET also acts as an AMPK activator, which leads to the inhibition of mTORC1 activity. mTORC1 is a downstream target of Akt signaling. Inactivation of Akt/mTORC1 and its downstream S6K1 can promote autophagy, a process involved in PD pathogenesis. Based on their mechanisms and potential benefits, we evaluated the potential protective effect of pretreatment with combinations of MET and RAPA in a 1-methyl-4-phenylpyridinium ion (MPP + )-treated SH-SY5Y neuronal cell model of PD. The results showed that MET and RAPA combinations lowered cell viability after exposure to MPP + . Increased LC3-II levels by MPP + were not altered by MET and RAPA pretreatment. In normal neuronal cells, MET and RAPA pretreatment inhibited the phosphorylation of both Akt and S6K1, and the phosphorylation remained suppressed after MPP + exposure. These findings suggest that when cells were exposed to MPP +, suppressed phosphorylation of both Akt and S6K1 by the MET and RAPA combination may lead to an inappropriate autophagic response, resulting in increased cell death.